2021
DOI: 10.20944/preprints202104.0095.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Management Intervention of Elderly Hypertension: A Literature Review

Abstract: Background: Indonesia is an archipelago with various cultured, will bee affects all aspects of people's lives, including beliefs related to health behavior and health care. One problem that needs serious attention is the elderly group because the elderly are a vulnerable group who have a high risk of experiencing health problems, such as anemia with hypertension, so they need good care management. The research objective was to determine self-management intervention for hypertensive elderly. Methods: This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The study entitled "Self-Management Intervention Of Elderly Hypertension: A Literature Review" revealed that self-care management in hypertension consists of medication adherence, health monitoring, diet management, exercise management, work management, and emotional management. (Wijayanti & Pandin, 2021). According to Bandura (2006), elderly with hypertension who have high self-confidence in their abilities will make their self-care behavior better (Okatiranti dkk., 2017).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…The study entitled "Self-Management Intervention Of Elderly Hypertension: A Literature Review" revealed that self-care management in hypertension consists of medication adherence, health monitoring, diet management, exercise management, work management, and emotional management. (Wijayanti & Pandin, 2021). According to Bandura (2006), elderly with hypertension who have high self-confidence in their abilities will make their self-care behavior better (Okatiranti dkk., 2017).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%